Development and Testing of a Control System for the Automatic Flight of Tethered Parafoils. Issue 3 (16th May 2016) - Coleman, Joseph; Ahmad, Hammad; Toal, Daniel
Abstract : This paper presents the design and testing of a control system for the robotic flight of tethered kites. The use of tethered kites as a prime mover in airborne wind energy is undergoing active research in several quarters. There also exist several additional applications for the remote or autonomous control of tethered kites, such as aerial sensor and communications platforms. The system presented is a distributed control system consisting of three primary components: an instrumented tethered kite, a kite control pod, and a ground control and power takeoff station. A detailed description of these constituent parts is provided, with design considerations and constraints outlined. Flight tests of the system have been carried out, and a range of results and system performance data from these are presented and discussed.